Effect of customised supplement on haemato-biochemical profile, serum minerals, metabolic hormones, antioxidant capacity and gene expression in crossbred calves - CHAUDHARY, SANDEEP K; DUTTA, NARAYAN; JADHAV, S E; PATTANAIK, A K (The Indian Journal of Animal Sciences, 2023)
Present experiment examined the supplementary effect of a tailor-made supplement to farmers’-based diet in crossbred calves. Male crossbred calves (15) were randomly allocated in 3 dietary treatments consisting of 5 calves in each. The dietary treatments were: Control- cereal straw-based diet with concentrate mixture as per the farmers’ practices; CS (customised supplement)- control diet with additional customised supplement @ 0.25% of BW; SD-standard diet. Serum glucose was higher in SD than control, however, CS had an intermediate response. The serum macro (Ca and i-P) and trace (Zn, Cu, Fe and Mn) minerals were higher in SD and CS than control. The serum T3 and T4 hormones were significantly higher in SD and CS than control group. The serum growth hormone (GH) and insulin-like growth factor-1 (IGF-1) were significantly higher in SD than control groups, however, SD had an intermediate position. The total antioxidant capacity (TAOC) was significantly higher in SD and CS than control group. The relative mRNA expression of cytokines, viz. IL-2 and IL-4 was significantly higher in SD and CS than control group. The relative mRNA expression of leptin (LEP) was significantly higher and ghrelin (GHRL) was significantly lower in SD than control group, however, CS had a transitional position. Thus, it can be concluded that supplementation of the customised supplement (@ 0.25% BW) to farmers’-based diet significantly improved the serum glucose concentration, metabolic hormone profile, antioxidant capacity and relative mRNA expression of cytokines and genes involved in energy metabolism in crossbred calves.